The invariable, the norm and the unknown: the emergence of modern Brazilian architecture in debate - Pignaton, Clara Bonna (Risco - Journal of Architecture and Urbanism, 2021)
This article presents the conflicts arising from the emergence of modern language in Brazil in the field of architecture through debates in public vehicles such as newspapers and congresses. The discussion between architects and thinkers such as Flávio de Carvalho, Mario de Andrade and Le Corbusier elucidate the concerns of the time, being them the construction of a national identity, progress, normalization, as well as the dialectic between rationality and emotions.